2019
DOI: 10.2174/1381612825666190110143258
|View full text |Cite
|
Sign up to set email alerts
|

The Esophageal Cancer and the PI3K/AKT/mTOR Signaling Regulatory microRNAs: a Novel Marker for Prognosis, and a Possible Target for Immunotherapy

Abstract: The Phosphatidylinositol 3-kinase/AKT/Mammalian Target of Rapamycin (PI3K/AKT/mTOR) pathway has a critical regulatory role in cell biology including translation, transcription, and autophagy. Dysregulation of this pathway is involved in the pathogenesis, development, and prognosis of esophageal cancer that has been assessed in the recent years and its potential as a target in therapy. This report summarizes the current knowledge about PI3K/AKT/mTOR pathway and its cross-talk with a focus on the value of target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 69 publications
0
31
0
Order By: Relevance
“…Our data showed that SLBZ-AP Many researchers confirmed that PI3K/Akt/mTOR signaling pathway is related to a few biological activities to affect cell proliferation, survival, and migration [7,8], especially to stimulate proliferation, survival, invasion/metastasis, and metabolic reprogramming and suppress autophagy, which is involved in possible mechanisms of oncogenic transformation [9]. PI3K/Akt/mTOR signaling pathway is commonly activated and suppression of its activation may inhibit cells proliferation and metastasis in cancers of the lung [10,11,50], colorectal [51,52], esophagus [53], breast [54][55][56], liver [57,58], and kidney [59,60], which has been considered a promising therapeutic target. Whether the PI3K/Akt/mTOR signaling pathway involved in SLBZ-AP affects BMLC was further explored in our study, results of which indicated that the mRNA and protein expression of AKT, mTOR, P70S6, and VEGF as well as protein expression of p-AKT, p-mTOR, p-P70S6, and VEGF was significantly increased in the marrow of tibia from BMLC mice.…”
Section: Discussionmentioning
confidence: 93%
“…Our data showed that SLBZ-AP Many researchers confirmed that PI3K/Akt/mTOR signaling pathway is related to a few biological activities to affect cell proliferation, survival, and migration [7,8], especially to stimulate proliferation, survival, invasion/metastasis, and metabolic reprogramming and suppress autophagy, which is involved in possible mechanisms of oncogenic transformation [9]. PI3K/Akt/mTOR signaling pathway is commonly activated and suppression of its activation may inhibit cells proliferation and metastasis in cancers of the lung [10,11,50], colorectal [51,52], esophagus [53], breast [54][55][56], liver [57,58], and kidney [59,60], which has been considered a promising therapeutic target. Whether the PI3K/Akt/mTOR signaling pathway involved in SLBZ-AP affects BMLC was further explored in our study, results of which indicated that the mRNA and protein expression of AKT, mTOR, P70S6, and VEGF as well as protein expression of p-AKT, p-mTOR, p-P70S6, and VEGF was significantly increased in the marrow of tibia from BMLC mice.…”
Section: Discussionmentioning
confidence: 93%
“…Membrane kinases including epidermal growth factor receptor (EGFR) are activated by external growth factors, which initiate receptor dimerization and subsequent events to activate these intracellular pathways. AKT has multiple targets to modulate a variety of proliferative and antiproliferative signaling processes, such as survival, apoptosis, angiogenesis, cell cycle, cell-cycle energy, and DNA repair [17][18][19][20][21][22]. Additionally, Lianghai Wang et al showed that the elevation of SOX9 inhibits the transcription of miR-203a by binding to the miR-203a promoter, thereby abolishing miR-203a-mediated impediment of PI3K/AKT/ mTOR pathway [23].…”
Section: Discussionmentioning
confidence: 99%
“…These signaling had crucial roles in cancer cells. For example, PI3K/AKT pathway was activated in EC samples ( Javadinia et al, 2018 ). Using specific inhibitors targeting this pathway significantly inhibited cell proliferation, enhancing apoptosis in EC cells ( Shi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%